If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5(2y + -1) = 2y + -4(y + 1) Reorder the terms: 3 + 5(-1 + 2y) = 2y + -4(y + 1) 3 + (-1 * 5 + 2y * 5) = 2y + -4(y + 1) 3 + (-5 + 10y) = 2y + -4(y + 1) Combine like terms: 3 + -5 = -2 -2 + 10y = 2y + -4(y + 1) Reorder the terms: -2 + 10y = 2y + -4(1 + y) -2 + 10y = 2y + (1 * -4 + y * -4) -2 + 10y = 2y + (-4 + -4y) Reorder the terms: -2 + 10y = -4 + 2y + -4y Combine like terms: 2y + -4y = -2y -2 + 10y = -4 + -2y Solving -2 + 10y = -4 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -2 + 10y + 2y = -4 + -2y + 2y Combine like terms: 10y + 2y = 12y -2 + 12y = -4 + -2y + 2y Combine like terms: -2y + 2y = 0 -2 + 12y = -4 + 0 -2 + 12y = -4 Add '2' to each side of the equation. -2 + 2 + 12y = -4 + 2 Combine like terms: -2 + 2 = 0 0 + 12y = -4 + 2 12y = -4 + 2 Combine like terms: -4 + 2 = -2 12y = -2 Divide each side by '12'. y = -0.1666666667 Simplifying y = -0.1666666667
| 6w-13=11 | | 5x=-34 | | 16=p+28 | | -2x-5=3x+10 | | -8x-10y=-24 | | 9(m-5)=128 | | 800y=24000 | | 2(4m+6)-27= | | -4+2h+12=2(-3h-4) | | a+3b=13 | | 3x^2+5x+21=0 | | 800y=84000 | | 2x-6x+3x+5x= | | -8x+6y=40 | | 8+r=-21 | | -3+c=5 | | 2y+11=13 | | 8x-2y=3 | | 3(5z-4)-16= | | (6x^2-x+9)+(2x^2+4x-8)= | | -5+a=9 | | x/8-4=15/16 | | 12.8/w=8 | | 3x^3-3x^2-6x= | | P=-2+5 | | 5=7-v | | 15+4v=8v+7 | | ac+xc+aw^2+aw^2= | | y+20+10x=20+9x | | -16x+80x+5=0 | | 6x+2x=10+8 | | (6k+10)-(k-8)= |